Neuroprotective Effects of Myrtenal in an Experimental Model of Dementia Induced in Rats - Stela Dragomanova; Stoyan Pavlov; Desislava Marinova; Yordan Hodzev; Maria Cristina Petralia; Paolo Fagone; Ferdinando Nicoletti; Maria Lazarova; Elina Tzvetanova; Albena Alexandrova; Reni Kalfin; Lyubka Tancheva (MDPI AG, 2022)
There is growing attention on natural substances capable of stimulating the cholinergic system and of exerting antioxidant effects, as potential therapeutic agents in Alzheimer's disease (AD). The aim of the present study is to evaluate the expected neuroprotective mechanisms of myrtenal (M) in an experimental model of dementia in rats. Dementia was induced in male Wistar rats by scopolamine (Sc) administration (0.1 mg/kg for 8 days and 20.0 mg/kg on day 9). The animals were divided into 5 groups (1) Controls; (2) Sc; (3) Sc + Myrtenal (40 mg/kg), (4) Sc + Galantamine (1 mg/kg); (5) Sc + Lipoic acid (30 mg/kg). Changes in recognition memory and habituation were evaluated via the Novel Object Recognition and Open Field tests. Acetylcholinesterase (AChE) activity, ACh levels, and changes in oxidative status of the brain were measured biochemically. The histological changes in two brain regions-cortex and hippocampus, were evaluated qualitatively and quantitatively. Myrtenal improved recognition memory and habituation, exerted antioxidant effects and significantly increased ACh brain levels. Histologically, the neuroprotective capacity of myrtenal was also confirmed. For the first time, we have demonstrated the neuroprotective potential of myrtenal in an experimental model of dementia. Our study provides proof-of-concept for the testing of myrtenal, in association with standard of care treatments, in patients affected by cognitive decline.